Population distribution in County Sligo - Freeman, T. W. (Statistical and Social Inquiry Society of Ireland, 1944)
County Sligo had 180,886 inhabitants in 1841 and 67,447 in 1936, a decrease of 62.6 per cent. The eleven counties with an even more marked decline include Leitrim and Roscommon, but not Mayo, which had a decrease of 58.8 per cent. The density of population per square mile in Sligo was 240 in 1841, 135 in 1891 and 96 in 1936. The counties more densely peopled include Dublin, Cork, Limerick and Waterford, which have the chief towns of Eire within their borders, Louth and Wexford, both of which have a considerable urban population, and three counties with a comparatively small area of unproductive land, namely, Carlow, Monaghan, and Cavan. Sligo is relatively densely peopled, for one-third of its area is mountain and lowland bogland. In 1891, almost one-quarter of the county was congested, with nearly 30 per cent of the population. As a result of heavy emigiation, only one d e d of the county would be congested on a 1936 re-assessment.
Read on Friday, 25th February, 1944
Keywords: Population distribution; Sligo; 314.15